2016
DOI: 10.14474/ptrs.2016.5.4.193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual restriction and unstable base dual-task training on balance and concentration ability in persons with stroke

Abstract: Objective: In the present study, the effects of visual restriction and unstable base dual-task training (VUDT), stable base dual-task training (SDT), and on stroke patients' balance and concentration abilities were examined. Design: Two-group pretest-posttest design. Methods: Dual-task training was conducted for thirty persons with chronic stroke who were hospitalized or receiving physical therapy and were randomly assigned to either the VUDT group (n=15) or the SDT group (n=15). The subjects were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It was assumed that the improvement in VD-SB balance training group could be due to the fact that the manipulation of visual input was more effective than the manipulation of standing surface to reweighting sensory information in the field of balance activity. Previous studies found that the exercise training with visual restriction by stroke patient affected their gait dynamic stability 27 ) knee joint proprioception 28) , balance and concentration ability 29 ) , gait velocity and balance 7) . Results of the present study extended previous results indicating that a training program with visual restrictions could improve the balance ability in persons with stroke more than training at free vision conditions 28,30) .…”
Section: Discussionmentioning
confidence: 98%
“…It was assumed that the improvement in VD-SB balance training group could be due to the fact that the manipulation of visual input was more effective than the manipulation of standing surface to reweighting sensory information in the field of balance activity. Previous studies found that the exercise training with visual restriction by stroke patient affected their gait dynamic stability 27 ) knee joint proprioception 28) , balance and concentration ability 29 ) , gait velocity and balance 7) . Results of the present study extended previous results indicating that a training program with visual restrictions could improve the balance ability in persons with stroke more than training at free vision conditions 28,30) .…”
Section: Discussionmentioning
confidence: 98%
“…Methods used to improve balance and gait of stroke patients include training using functional electrical stimulation [ 8 ], dual task exercise [ 9 ], therapeutic approach through collaborative action of Brunstrom [ 10 ], virtual environment rehabilitation [ 11 ], mirror therapy [ 12 ], and so on. Among them, mirror therapy is one of treatments for patients with brain lesions based on the theory of neuroplasticity in the brain.…”
Section: Introductionmentioning
confidence: 99%